(1100) The Representative Model of Economic Time-Series النموذج التمثيلى للسلسلة الزمنية الاقتصادية - Josef Kozak. (the institute of national planning, 2018)
in the last few years the author has been working with my colleagues at the institute of statistics of the prague school of economic in the field of the time-series analysis of selected economic indicators of the post-war Czechoslovak economy. In this study there is an explanation of the basic features of this not yet considered concept of time-series of economic indicators.